Development of the model of the antagonistic agents behavior under a cyber conflict - Milov, Oleksandr; Yevseiev, Serhii; Ivanchenko, Yevheniia; Milevskyi, Stanislav; Nesterov, Oleksandr; Puchkov, Oleksandr; Salii, Anatolii; Timochko, Oleksandr; Tiurin, Vitalii; Yarovyi, Аleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
The results of the development of the model of the antagonistic agents behavior in a cyber conflict are presented. It is shown that the resulting model can be used to analyze investment processes in security systems, taking into account the assumption that investment processes are significantly influenced by the behavior of parties involved in a cyber conflict. General approaches to model development are presented. First of all, the system of concepts, assumptions and limitations is formed, within the framework of which a mathematical model of behavior must be developed. Taking this into account, the mathematical model of the conflicting agents behavior, presented in the form of algebraic and differential equations, is developed. The developed model presents both the technical characteristics of the security system and the psychological characteristics of the participants in the cyber conflict, which affect the financial characteristics of the investment processes in cybersecurity systems. A distinctive feature of the proposed model is the simultaneous consideration of the behavior of the parties to a cyber conflict not as independent parties, but as agents mutually interacting with each other. The model also makes it possible to simulate the destabilizing effect of the confrontation environment disturbances on the behavior of the conflicting parties, changing the degree of vulnerability of the cybersecurity system along various attack vectors and the level of their success. Using the developed model, simulation modeling of the interacting agents behavior in a cyber conflict is performed. The simulation results showed that even the simplest behavior strategies of the attacking side (“the weakest link”) and the defense side (“wait and see”) make it possible to ensure information security of the business process loop. The developed model of interaction between the attacker and the defender can be considered as a tool for modeling the processes of the conflicting parties behavior when implementing various investment scenarios. The simulation results enable decision-makers to receive support regarding the direction of investment in the security of the business process loop.